Atrial fibrillation type and renal dysfunction as important predictors of left atrial thrombus. Issue 17 (30th April 2019) - Kapłon-Cieślicka, Agnieszka; Budnik, Monika; Gawałko, Monika; Peller, Michał; Gorczyca, Iwona; Michalska, Anna; Babiarz, Aldona; Bodys, Aleksandra; Uliński, Robert; Żochowski, Maciej; Scisło, Piotr; Kochanowski, Janusz; et al.
Abstract : Objective: We aimed to identify predictors of left atrial appendage (LAA) thrombus in patients with atrial fibrillation (AF) and to enhance the prognostic value of the CHA2 DS2 -VASc score. Methods: Derivation cohort included 1033 consecutive AF patients referred for catheter ablation or direct current cardioversion, in whom transoesophageal echocardiography (TOE) was performed prior to the procedure. Logistic regression analysis was used to identify predictors of LAA thrombus on TOE. Receiver operating characteristic (ROC) curves were constructed to compare the newly developed score with the CHA2 DS2 and CHA2 DS2 -VASc scores in the derivation and the validation (n=320) cohort. Results: On TOE, LAA thrombus was present in 59 (5.7%) patients in the derivation cohort. Aside from variables encompassed by the CHA2 DS2 -VASc score, LAA thrombus predictors included AF type (persistent/'permanent' vs paroxysmal) and renal dysfunction. These predictors were incorporated into the CHA2 DS2 -VASc score. In ROC analysis, area under the curve (AUC) for the new score (CHA2 DS2 -VASc-RAF score) was significantly higher (0.81) than those for the CHA2 DS2 and CHA2 DS2 -VASc scores (0.71 and 0.70, respectively). In the validation cohort, the CHA2 DS2 -VASc-RAF score also performed significantly better (AUC of 0.88) than the CHA2 DS2 and CHA2 DS2 -VASc scores (AUC of 0.63 and 0.60, respectively). Conclusion: In real-world AF patients with majority on oral anticoagulation, LAA thrombus was found in approximately 6%. Two variables not included in the CHA2 DS2 -VASc score (AF type and renal dysfunction) proved strong, independent predictors of LAA thrombus and might improve thromboembolic risk stratification.